The shadow puppet theatre of Malaysia : a study of wayang kulit with performance scripts and puppet designs - Osnes, Beth (McFarland & Co., 2010)
"This book explores the Malaysian form of shadow puppet theatre, highlighting its nature within the context of Southeast Asian shadow puppet theatre traditions. An examination of the Malaysian puppet tradition is provided, as well as performance scripts, designs for characters, instructions for a shadow screen, and easy directions. An additional section considers the practical, pedagogical, and ethical issues"--Provided by publisher.